Nunatsiavut, ‘our beautiful land’: Inuit landscape ethnoecology in Labrador, Canada - Cuerrier, Alain; Clark, Courtenay; Dwyer-Samuel, Frédéric; Rapinski, Michel (Botany, 2022)
International audience For Inuit in the subarctic transition zone of northeastern Canada, an intimate knowledge of the environment and local biodiversity is crucial for successful traditional activities. This study examines what kinds of landscape features and habitats Inuit of Nunatsiavut recognize and name. During interviews, community members (mostly Elders) were shown photographs from the region and were asked to describe and name salient types of places in Labrador Inuttitut. The most frequently reported geographical units dealt with the region’s topography (e.g., mountain, island, flat-place), hydrology (e.g., river, bay), and superficial characteristics (e.g., bedrock, permanent snow patch). Ecological considerations were also prominent, such as plant associations and animal habitats (e.g., shrubby-place, wetland, caribou-return-to-place). Areas were often characterized by a dominant species or substrate type, being named using the plural form of the species and (or)substrate (e.g., “napâttuk” meaning ‘tree’ and “napâttuit” meaning ‘forest’ or “siugak” meaning ‘sand’ and “siugalak” meaning ‘sandy-area’). Some types of places reported by Inuit were significant mainly for traditional activities (e.g., berry-patch, seal-place, dry-wood-place, danger-place), aiding navigation and resource finding. Integrating Inuit conceptions of ecosystems and their component landscape units with those of contemporary science can improve our understanding of subarctic ecology, benefit climate change adaptation strategies, and Inuit language as well as culture conservation initiatives. Pour les Inuits de la zone de transition subarctique du nord-est du Canada, une connaissance intime de l’environnement et de la biodiversité locale est essentielle au succès des activités traditionnelles. Cette étude examine quels types de caractéristiques du paysage et d’habitats les Inuits du Nunatsiavut reconnaissent et nomment. Au cours des entrevues, des membres de la communauté (principalement des aînés) ont vu des photographies de la ...